Production Scheduling Optimization to Minimize Makespan and the Number of Machines with Mixed Integer Linear Programming. Issue 1 (January 2021) - Farizal, F; Gabriel, D S; Rachman, A; Rinaldi, I
Abstract: In production management field, production efficiency can be improved through minimizing machine downtime, optimizing production scheduling, minimizing inventory of raw materials and finished products. In this research, the production efficiency is improved through optimizing production schedule that has two goals; not only minimizing production makespan but also minimizing the number of machines used. For the purpose, a mixed integer linear programming (MILP) model was developed. The model was used to solve a problem producing 6 products with 4 production lines. In this study, product demand was first forecasted with Autoregressive Integrated Moving Average (ARIMA) method. Optimization results comes up with makespan of 295.4 hours using only one production line. As addition, this research is also dealing with three real life production scenarios.